2017
DOI: 10.1111/ecc.12664
|View full text |Cite
|
Sign up to set email alerts
|

The musculoskeletal consequences of breast reconstruction using the latissimus dorsi muscle for women following mastectomy for breast cancer: A critical review

Abstract: Breast reconstruction using the latissimus dorsi (LD) flap following mastectomy is an important management option in breast cancer. However, one common, but often ignored, complication following LD flap is shoulder dysfunction. The aim of this critical review was to comprehensively assess the musculoskeletal impact of LD breast reconstruction and evaluate the functional outcome following surgery. Five electronic databases were searched including; Medline, Embase, CINAHL Plus (Cumulative Index to Nursing and Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 51 publications
(166 reference statements)
0
21
0
Order By: Relevance
“…A number of papers report on the sequelae after harvest of the LD flap in regard to shoulder function, however the evidence is ambiguous. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The aim of this study was to evaluate and compare, systematically for the first time, the shoulder-related morbidity associated with delayed breast reconstruction using either of the two flaps.…”
Section: Conclusion Introductionmentioning
confidence: 99%
“…A number of papers report on the sequelae after harvest of the LD flap in regard to shoulder function, however the evidence is ambiguous. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The aim of this study was to evaluate and compare, systematically for the first time, the shoulder-related morbidity associated with delayed breast reconstruction using either of the two flaps.…”
Section: Conclusion Introductionmentioning
confidence: 99%
“…Most studies agree however that the functional deficit in the shoulder following transfer of the LD muscle is worst in the first three to six months following surgery, and recovers close to baseline at the one year mark. [10][11][12][13][14][15] However, some functional studies have also found objective loss of torque strength of the shoulder a few years after surgery. 16,17 The primary objective of this study was to study the effect of breast reconstruction using the LD flap on patient reported shoulder function, as well as quality of life, using the Breast-Q questionnaire, compared with a control group of women who underwent total mastectomy without breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The papers focused primarily on LDBR procedure and in every paper, the final number of points for the main part of DASH and the additional module discussed in the paper was lower than 20, indicating slight disability in everyday life and work, while the results of an additional module regarding sport/playing an instrument varied greatly-from 2.9 to 84.3 [15]. In another systematic review from 2016, the extreme differences in DASH results of post-LDBR patients were noted [29]. On the basis of the author's own research as well as research by other authors, it may be assumed that LDF breast reconstruction procedure causes decrease of functionality and life quality, especially in the time period immediately after the procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Research by Huizum et al also showed the significant difference of DASH results between post-LDBR patients and healthy subjects, which additionally correlated with the upper limb muscle strength decrease [28]. Other authors point out the fact of upper limb muscle strength decrease as well [10,29,30]. A systematic literature review from 2014 includes seven papers using DASH to assess functional ability and life quality after procedures using LDF.…”
Section: Discussionmentioning
confidence: 97%